Assessing the banking sector of Bosnia and Herzegovina: An analysis of financial indicators through the MEREC and MARCOS methods - Zoran Mastilo; Anelka Štilić; Dejan Gligović; Adis Puška (Journal of Central Banking Theory and Practice, 2024)
The banking sector assumes a pivotal role in the economic development of nations. The assessment of financial indicators pertaining to banks holds fundamental importance in the evaluation of bank stability and sustainability. This research employs the MEREC (Method based on the Removal Effects of Criteria) and MARCOS (Measurement of Alternatives and Ranking according to COmpromise Solution) methodologies to delve deeper into the financial landscape of the banking sector in Bosnia and Herzegovina (BiH). Specifically, the objective is to rank banks according to their financial indicators, utilizing financial data from the year 2022. The MEREC method is applied to gauge the significance of financial indicators and ascertain their respective weights, while the MARCOS method is employed to rank banks within BiH based on their financial indicators. The examination of financial indicators within the BiH banking sector, facilitated by the MEREC and MARCOS methodologies, yields a more comprehensive understanding of the sector's present condition. Limitations of this research, which primarily stem from its reliance on available financial data and predefined methodologies, lies within limited consideration for external factors. To provide a broader contextual perspective, the inclusion of additional financial indicators and comparative analyses with banking sectors of other nations would be imperative. The findings of this research reveal that Raiffeisen Bank exhibits the most favourable financial indicators and demonstrates the highest level of efficiency within this context. Consequently, this research offers insights into identifying exemplary banks that can serve as models for enhancing the performance of others.
Keywords: C58; C60; G21; 330; financial indicators; banks; Bosnia and Herzegovina; MEREC method; MARCOS method